COMPREHENSIVE EVALUATION OF THERMAL PERFORMANCE AND TIME-LAG IN RESIDENTIAL APARTMENTS IN AMMAN: Received: 06th February 2024 Revised: 08th February 2024, 22nd February 2024, 22nd April 2024 Accepted: 22nd February 2024 - Dalia Salah; Ramzi Qasmeem Alrefaee (MATTER: International Journal of Science and Technology, 2024)
This exploration investigates the potential of enhancing energy efficiency in residential structures in Amman, Jordan, by introducing an innovative material termed "Phase Transition Substance with Fungal Integration (PTSF)." Through computational simulations using Autodesk-Revit, the analysis evaluates the thermal efficiency of a standard residential building, contrasting traditional construction materials with PTSF. The study centers on three crucial elements: outer walls (W.01), roof (R.01), and ground level slab (S.01), all initially not meeting prescribed thermal conductivity regulations. Integration of PTSF notably improves the thermal efficacy of the building’s shell, aligning with Jordanian standards for thermal insulation. Furthermore, a systematic examination explores the time delay of materials within the residential envelope, revealing an average lag of approximately 8 hours. This lag implies that, with the incorporation of the PTSF layer, the envelope requires 8 hours to transmit external temperatures (e.g., 30°C) to attain the interior’s peak temperature, underscoring the material’s potential in curbing energy consumption.